PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ALAM BERDIKARI MANDIRI CIREBON - Abdul Djalil; Bunga Astra Gracia (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of Motivation and Work Discipline on Employee Performance at PT Alam Berdikari Mandiri Cirebon, both partially and simultaneously. This research uses an associative quantitative approach. The population in this study was all 70 employees. The sampling technique used a saturated sampling technique with the sample in this study being 70 employees. The type of data used is primary and secondary. The data analysis techniques used are descriptive statistical analysis, data instrument tests, classical assumption tests, simple and multiple linear regression tests, hypothesis testing via the t test and F test, as well as correlation coefficient tests and determination. The research results show that motivation partially has a positive and significant effect on employee performance. This is shown by the tcount value of 57.397 > 2.002 ttable value with a significant value of 0.000 <0.05, then work discipline has a positive and significant effect on employee performance. This is indicated by the tcount value of 2.454 > 2.002 ttable value with a significant value of 0.000 < 0.05. Simultaneous testing shows that motivation and work discipline simultaneously have a positive and significant effect on employee performance, this is indicated by the Fcount value of 808.299 > 3.159 Ftable value with a significance value of 0.000 <0.050. The R-Square value of 0.966 indicates that motivation and work discipline influence employee performance by 96.6%, while the rest is influenced by other variables.